Do poor-responder patients benefit from increasing the daily gonadotropin dose during controlled ovarian hyperstimulation for IVF?. (16th September 2014) - Haas, Jigal; Zilberberg, Eran; Machtinger, Ronit; Kedem, Alon; Hourvitz, Ariel; Orvieto, Raoul
Abstract: We aim to assess the in vitro fertilization-embryo transfer (IVF-ET) outcome in patients receiving an extremely high 450 daily dose (IU) of gonadotropins during controlled ovarian hyperstimulation (COH) for IVF. Moreover, in those who failed to conceive while using 450 daily dose (IU) of gonadotropins, we aim to evaluate whether increasing the daily dose gonadotropins to 600 IU will improve IVF outcome. All consecutive women, admitted to our IVF unit and underwent COH consisting of daily gonadotropin dose of 450 IU were included. Ovarian stimulation characteristics, number of oocytes retrieved, number of embryo transferred and pregnancy rate were assessed. Nine-hundred one consecutive IVF cycles were evaluated. While there was no between-group difference in the duration of COH, patients who conceived were significantly younger, yielded higher number of oocytes retrieved and embryos transferred and had significantly lower cancellations. In a sub-analysis, including only those patients who failed to conceive while using 450 daily dose (IU) of gonadotropins, and who underwent a subsequent IVF cycle attempt with the used of 600 IU daily dose of gonadotropins, no improvements in COH characteristics or cancellation rates were observed with increasing the daily gonadotropin dose to 600 IU. To conclude, in poor responders undergoing COH with an extremely high daily gonadotropin dose (450 IU), the most important factors that predict IVF success are female age and the number of oocytes retrieved. Moreover, patients who failed to conceive on a daily gonadotropin dose of 450 IU will not benefit from increasing the dose to 600 IU and should therefore consider the options of egg donation or adoption. Chinese abstract: 本研究目的在于评估在控制性卵巢超刺激（COH）阶段每日给予超大剂量促性腺素（450 IU/天）对患者体外受精-胚胎移植（IVF-ET）结果的影响。此外，对于给予促性腺素每日剂量450 IU治疗失败的患者，我们将剂量增至600 IU，评估她们IVF的结局。研究对象为本IVF中心接受COH治疗且每日应用促性腺素剂量为450 IU的患者。评估指标包括卵巢刺激特征、获卵数、胚胎移植数及妊娠率。本研究共纳入了901例连贯的IVF治疗周期。COH阶段无组间差异，治疗成功的患者显著特征为年龄小、获卵数目与胚胎移植数目多且无效胚胎少。进一步研究仅包含应用促性腺素450 IU每日治疗失败，且愿意尝试在接下来的治疗周期中增加促性腺素剂量至600 IU每日的患者，但结果显示增加剂量并未改善COH特征与无效胚胎率。结果表明，卵巢反应性低下的患者在接受每日超大剂量促性腺素（450 IU）COH治疗时，最重要的影响IVF成功的因素是患者年龄与获卵数目。此外，若每日促性腺素剂量为450 IU治疗失败的患者，增加剂量至600 IU并不能使其获益，建议考虑卵子捐赠或领养途径。